PENERAPAN PROTOKOL ROUTING PROAKTIF OLSR PADA JARINGAN MOBILE AD HOC NETWORK (MANET) MENGGUNAKAN RASPBERRY PI UNTUK TRANSFER FILE - Rico Dwi Kurniawan; Muh. Yamin; LM. Fid Aksara (semanTIK, 2019)
The wireless network's users are increasingly used compared to wired networks. One of the developments of wireless networks is the existence of a technology called Ad Hoc network. Ad Hoc network is a solution where mobile devices such as laptops, tablets, smartphones, etc. can communicate with each other without the support of network infrastructure in the form of access points or means of supporting data transmission. Mobile Ad Hoc Network (MANET) is a multi-hop wireless network consisting of a collection of dynamic mobile nodes.Along with the development of technology, MANET began to be developed in anticipation if the central infrastructure of a network cannot be used. In this network, each node is a router that functions to determine the route that is closest to the nodes that communicate. Each node on the MANET network is also mobile so it is possible to be free to move, but this has an impact on the topology which keeps changing along with the movement of nodes.  In the test carried out file transfer is applied to the scenario of MANET infrastructure testing with three nodes with two conditions, namely the condition of the absence of interference with the MANET network and the condition when there is interference with the MANET network. file transfer testing on the MANET network can work in accordance with nature and network conditions that MANET has, but from the results of the analysis, the file transfer speed will decrease as the gateway nodes increase on the communication route between the node server and the client. Keywords—MANET, File Transfer Protocol (FTP), Optimized Link Stated Routing (OLSR)DOI : 10.5281/zenodo.2650753